Nursing care for symptoms seen in patients undergoing palliative surgery – a retrospective study - Uçar, Özge; Çelik, Sevim; Karahan, Elif; Altıntaş, Sibel (European Journal of Clinical and Experimental Medicine, 2023)
<p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Palliative care is an approach to improve the quality of life of patients and their families facing problems associated with life-threatening illnesses or old age, to manage their pain, distress, and other symptoms, improving their quality of life, and providing psychological support. This study was designed to identify the care practices planned by nurses for the health issues of palliative surgical patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This is a retrospective, cross-sectional, descriptive study. The data was collected from digital records of the two state hospitals in the Western Black Sea Region of Turkey between January 2019 and January 2020. The research was completed with a total of 391 data of patients undergoing palliative surgery. Frequency and percentage distributions were used in descriptive statistics. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The frequency of symptoms observed in patients were determined as cough and sputum (81.8%), dehydration (73.9%), dyspnea (71.9%), fatigue (49.9%), loss of appetite-weight (49.9%), insomnia (44%), pain (37.6%), nausea (29.2%), and constipation (23.8%). The planned nursing diagnoses for these symptoms were identified as risk for falls, imbalanced nutrition, risk for impaired skin integrity, risk for infection, risk for aspiration, deficient knowledge, risk for impaired respiratory function, constipation, ineffective airway clearance, pain, risk for deficient fluid volume, sleep deprivation, impaired gas exchange respectively. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. This study highlights the insufficient planning of nursing care for the symptoms of palliative surgical patients receiving palliative care in our country. Therefore, it is recommended that palliative care nurses be supported with in-service training on appropriate care planning topics.